Representações sobre o ensino-aprendizagem de língua inglesa: entre os documentos oficiais e a fala do professor da escola pública - Araújo, Gilberto Alves (Universidade Federal do Tocantins, 2016)
This research analyzes the teachers’ and a curricular proposal’s discourse under Discourse Analysis theory based on Pêcheux’s (1995, 1997a, 1997b, 2006) and Orlandi’s works (1998, 1999, 2004), taking into account the notions of forgetting, subjecting, interdiscourse and intradiscourse. Other authors’ conceptions regarding to identity, complexity ant literacy will also be taken into consideration. The analyzed data comprises selections inside of different materialities: excerpts from three English teachers’ interviews who works in Tocantins hinterland (Araguaína), as well as excerpts from state curricular proposal for foreign language teaching in high school, being the same proposal signed by technicians, teachers and professors from the state and other Brazilian regions. This document presents local orientations to teachers concerning the implementation of foreign language teaching. The main objective of this study is to identify discursive representations about English language teaching in school, whether from teachers’ or official discourse’s point of view, comparing consonances and dissonances. The results point out that teacher’s discourse builds English language teaching as a battle fought in hic et nunc while, in the silence of explicit references to curricular documents, it projects this same teaching in an extensive horizon of expectations with regard to teaching significancy; the official document discourse tends to overestimate the scientific and literary discourse in so far as it tends to consign the silence to teacher’s voice in his/her daily practice.